Union transfers to state of kerala and it’s impact on rural development-a study on MGNREGA - T.P. Akhila; Meghna Baburaj; P.N. Krishnapriya and C.V. Durgalashmi
This paper is formulated to analyze the Union transfers to the State Government for rural development and the level of awareness of beneficiaries in Kerala on such schemes emphasizing on MGNREGA. Mahatma Gandhi National Rural Employment Act, which was first named as National Rural Employment Guarantee Act, implemented in 2006, is a successful step by the Central Government to provide work to the unemployed and illiterate members of the society. Scheme has led to social, infrastructural, technological and political advances in the society. The main aim of the Government through such an initiative is to assure that no individual is left out from the Fundamental Right of ‘Right to Work’. MGNREGA act aims to provide unskilled manual work to all the capable and willing civilians of the nation. This research is undertaken to ensure the level of awareness of the prospective members of such beneficial Union schemes giving focus on MGNREGA and to ensure that the workers under the scheme are provided with all the benefits that they tend to receive as part of membership in the scheme to boost the rural economic development focusing on Thrissur and Palakkad districts of Kerala. Data analysis highlights the level of awareness of the workers about the benefits received and to be received under the scheme. The research concludes that like two sides of a coin, the benefits for prospective Beneficiaries vary from place to place based on economy, governance and geographic conditions.